Environmental impact calculations, life cycle cost analysis. Issue 2 (October 2014) - Nicholson, D.; Smith, P.; Bowers, G. A.; Cuceoglu, F.; Olgun, C. G.; McCartney, J. S.; Henry, K.; Meyer, L. L.; Loveridge, F. A.
Abstract : This session explored the evaluation and characterization of the sustainability of thermoactive geotechnical systems. Thermoactive geotechnical systems take advantage of shallow geothermal energy by using the foundation of a structure as a heat source and sink for use with a ground source heat pump. Methods for their evaluation within a sustainability framework still need to be developed. This can be done within larger regulatory frameworks such as the Code for Sustainable Homes. The Life Cycle Analysis methodology has been used to examine non-thermoactive geotechnical systems using both embodied carbon and embodied energy as metrics. Life Cycle Analyses have also been performed on ground source heat pumps and can provide valuable insight into the indirect operational environmental impacts of thermoactive geotechnical systems.